Publikasi Mimpi Bernuansa Politis di Tengah Antisipasi Radikalisme dalam Kajian Sadd al-Dzari`ah - Busyro, Busyro; Alwana, Hanif Aidhil; Ismail, Ismail (AL-ISTINBATH : Jurnal Hukum Islam, 2021)
This paper questions how to respond to the publication of political dreams in relation to efforts to reduce radicalism in Indonesia according to Sadd al-Dzari'ah's study. This research is qualitative in nature and its presentation uses descriptive analysis method. Publication of dreams is a common thing in society, moreover dreams that are disseminated are good dreams. However, sometimes the publication of a dream, according to people who experience it, is suitable for public consumption, on the other hand it may have an impact on the emergence of radicalism in a country. An example that recently occurred was the dream of Haikal Hassan who met Rasulullah SAW regarding the shooting of the Islamic Defenders Front (FPI) laskar by the police in Mega Mendung, West Java. The publication of this dream seemed to have political nuances and caused turmoil among the FPI, because in this dream Rasullullah SAW seemed to blame the police for handling the FPI laskar and on the contrary defending the FPI laskar who was killed. This paper concludes that the act of publishing dreams which was previously immutable is not permitted if the publication creates a radicalism movement that may threaten the integrity of the country. In the study of siyasah syar'iyyah, security and public order (maslahah) is a very important part of state politics. Therefore, according to Sadd al-Dzari'ah's study, the legal position of publishing dreams, which has so far been converting, can become haram if it causes harm to a country.